DESIGN AND CHARATERIZATION OF VAGINAL MUCHOADHESIVE FILMS CONTAINING VALACYCLOVIR HYDROCHLORIDE: A FACTORIAL STUDY - Maitham S Alathar, Pooja B C, TS Nagaraja, Yogananda R, Suban sab, Sreeharsha Nagaraja, Afzal Haq Asif, Girish Meravanige (South Eastern European Journal of Public Health, 2025)
Designing and characterizing the mucoadhesive vaginal film of valacyclovir hydrochloride is the primary goal of this work. 23 factorial designs are used in the formulation of the vaginal film. PEG 400, 2-Mercaptocthanol, and Ethyl Cellulose concentration were selected as independent factors, and thickness, tensile strength, and dissolution were selected as dependent variables. The improved batch was tested using FTIR and DSC, and its thickness, tensile strength, folding endurance, surface PH, percentage of drug release, and swelling index were further assessed. The F-OPT formulation and the pure drug's FTIR and DSC data show that the drug and polymer are compatible. The F-OPT formulation, out of all the formulations created, has remarkable results, with the highest percentage of drug release (96.92%) in 12 hours and the lowest swelling index (45.62%). Studies on the F-OPT formulation's short-term stability showed that it was stable. Therefore, valacyclovir HCL mucoadhesive vaginal films may be an appropriate formulation for treating genital herpes with a practical administration method.